Prospective comparison of laser nephelometry with standard agglutination techniques for detection of rheumatoid factor. Issue 2 (February 1987) - Prentice, A G; Hickling, P; Wiseman, I C; Holwill, C J; Northwood, J
Abstract : IgM rheumatoid factor was assayed by three routine methods: latex fixation; haemagglutination; and end point laser nephelometry in 69 patients with definite or classical rheumatoid arthritis and 58 patients with other non-rheumatoid arthropathies, selected prospectively according to the American Rheumatism Association clinical criteria. The operators of the assays were unaware of the clinical diagnoses. In the group with rheumatoid arthritis 75.4% were positive by latex fixation, 73.9% by haemagglutination, and 55.1% by nephelometry. In the group with non-rheumatoid arthropathies 10.4% were positive by latex fixation, 8.6% by haemagglutination, and 10.4% by nephelometry. Thus the simple and inexpensive latex fixation test was as good as the haemagglutination test, and both were significantly better than nephelometry in the laboratory confirmation of the clinical diagnosis of definite or classic rheumatoid arthritis (chi 2 = 5.40 and 4.56, and p less than 0.025 and less than 0.05, respectively). None of these tests was significantly better or worse than the others in producing positive results in the group with non-rheumatoid arthropathies.